Effectiveness of Implementing Qris Transactions in the Covid-19 Era in Medan Petisah Market - Kalsum, Umi (Journal of International Conference Proceedings, 2023)
In the Covid-19 era, the Minister of Health uses non-cash transactions, non-cash transactions that reduce interaction are the QRIS (Quick Response Code Standard Indonesian) payment system, with a QR Code Scan of a successful payment transaction. So according to the researchers, the Petisah market in Medan City is a place where cash transactions are often used, so it would be better if QRIS payments could be made at the petisah market in Medan City. The research used by researchers is empirical in that they go directly to the field to see the market situation and how effective the use of QRIS is to conduct interviews with business people in the petisah market in Medan City. Researchers obtained data from the Petisah market in Medan City. partially the perceived interest variable has no influence on the decision to use QRIS, while the perceived benefits and perceived risk variables have a significant influence on the decision to use QRIS at the Medan Petisah market. Simultaneously the variables perceived interest, perceived benefits and perceived risk together influence a significant relationship to the decision to use QRIS at Pasar Petisah Medan.